The dimensions of successful young adult development: A conceptual and measurement framework. Issue 3 (2nd July 2016) - Scales, Peter C.; Benson, Peter L.; Oesterle, Sabrina; Hill, Karl G.; Hawkins, J. David; Pashak, Travis J.
ABSTRACT: In this article, we draw on the theoretical and empirical literature to name what appear to be core dimensions of successful young adult development. We also describe some possible indicators and measures of those dimensions and sketch the kinds of developmental relationships and opportunities young people need in adolescence to effectively transition to a successful young adulthood, as well as the developmental relationships and opportunities young adults need for continued well-being. We name eight social, psychological, behavioral, educational, occupational, health, ethical, and civic dimensions of successful young adult development, and suggest that only a minority of adolescents are well-prepared to make a transition to successful young adulthood. The goal of the article is twofold: to contribute to the articulation of and consensus on the dimensions of successful young adult development, and to lay the groundwork for subsequent research to empirically validate both those core dimensions, as well as developmental indicators of progress toward attainment of these proposed dimensions of well-being.